Perbedaan pH Saliva Sebelum dan Sesudah Meminum Minuman Probiotik Yogurt pada Anak Penyandang Tunagrahita di Slb C Dhar- ma Rena Ring Putra II Yogyakarta - Syahputri, Hilma Yarisya Husna; Sulastri, Siti; Widayati, Aryani (Journal of Oral Health Care, 2019)
That isMentally-disabled children have below-average intelligence, affecting their cognitive and motor developments, so they are less able to maintain their dental and oral hygiene. Salivary pH is one that affects the condition around the teeth and mouth. Yoghurt is a probiotic drink which can prevent caries prevalence—determining the difference between salivary pH before and after consuming yoghurt probiotic alcohol among mentally- disabled children. This was a quasi-experimental research with the cross-sectional approach. The research design used one group, pretest and posttest. The research variables were salivary pH before and after consuming yoghurt probiotic drink. The research population was 46 men- tally-disabled students of SLB C Dharma Rena Ring Putra II Yogyakarta of 2018/2019 academic year. The sampling technique was purposive sampling on 31 mentally-disabled children. The data analysis was a paired sample t-test. The result of the paired-sample t-test showed that there was a significant difference between the salivary pH of mentally- disabled children before and after consuming yoghurt probiotic drink. The mean of salivary pH before is 7.08, which is based, and after 6.78, which is acidic. The probability value is 0.001<0.05. There was a difference between salivary pH of mentally- disabled children in SLB-C before and after consuming yoghurt probiotic drink.